2017
DOI: 10.6004/jnccn.2017.0138
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Survival in Metastatic Pancreatic Adenocarcinoma, 1993–2013

Abstract: During the past 2 decades, numerous clinical trials have focused on improving outcomes in patients with metastatic pancreatic cancer (mPDAC). The efficacy of new treatments has been demonstrated among highly selected patients in randomized phase III trials; hence, it is not clear to what extent these advances are reflected within the broader mPDAC population. Survival statistics were extracted from the SEER database for patients diagnosed with mPDAC between 1993 and 2013. Survival was analyzed using the Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 10 publications
1
42
1
Order By: Relevance
“…This is slightly superior to the survival found in the pivotal MPACT trial, that assessed the activity of the combination of Gemcitabine plus Nab‐Paclitaxel in the first‐line setting . It also exceeds by far the overall survival of patients assessed through national cancer databases, highlighting the potential benefit of centralized pancreatic cancer also in the metastatic setting . Therefore, we believe the incorporation of new chemotherapeutic regimens and treatment techniques has favorably impacted the outcomes of patients with advanced pancreatic cancer in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…This is slightly superior to the survival found in the pivotal MPACT trial, that assessed the activity of the combination of Gemcitabine plus Nab‐Paclitaxel in the first‐line setting . It also exceeds by far the overall survival of patients assessed through national cancer databases, highlighting the potential benefit of centralized pancreatic cancer also in the metastatic setting . Therefore, we believe the incorporation of new chemotherapeutic regimens and treatment techniques has favorably impacted the outcomes of patients with advanced pancreatic cancer in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Data between 1974 and 2013 has demonstrated that the overall increase in the incidence of PAAD is associated with risk factors such as smoking, obesity and diabetes in the USA (2). In recent decades the proportion of patients with metastatic PAAD with survival time >1 year has increased significantly, but the proportion of deaths within 2 months is still considerable (50.6%; P<0.001) (3). The median overall survival (OS) is ~16 months after resection in patients with non-metastatic pancreatic ductal adenocarcinoma, but the resectability rate is also low, <10% (4).…”
Section: Introductionmentioning
confidence: 99%
“…Median all stage overall pancreatic cancer survival has been reported as 14 months for those with a pathogenic BRCA1/2 variant [6]. For reference, those with metastatic pancreatic cancer generally have an estimated median survival below 6 months [7,8]. Following clear margin removal of a pancreatic tumor, median survival time increases to around 23 months [8,9].…”
Section: Introductionmentioning
confidence: 99%